Impact of radiation therapy on fatigue at 1 year in breast cancer survivors in the prospective multicentre CANcer TOxicity cohort. (December 2022) - Ghannam, Youssef; Di Meglio, Antonio; Sarrade, Thomas; Jacquet, Alexandra; Everhard, Sibille; Kirova, Youlia; Peignaux, Karine; Guilbert, Philippe; Charra-Brunaud, Claire; Blanchecotte, Julien; Bochaton, Odile Fargier; Pasquier, David; et al.
Abstract: Background: Fatigue is a common and disabling symptom after breast cancer (BC) treatment, significantly impacting patients' quality of life. We aimed to assess the impact of radiation therapy (RT) modalities on fatigue one year after treatment among patients with early-stage BC. Methods: We used CANTO-RT, a subcohort of CANcer TOxicity (CANTO; NCT01993498), a multicentric nationwide prospective cohort of stages I–III BC treated from 2012 to 2017. Our primary outcome was severe global fatigue 1 year after RT completion (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 score ≥40/100). The secondary outcomes included severe physical, emotional and cognitive fatigue (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-FA12). RT-related variables were used as independent variables. Multivariable logistic regression models assessed associations between RT-related variables and fatigue. Results: The final analytic cohort included 3295 patients. The prevalence of severe global fatigue 1 year after treatment was 33.3%. Internal mammary chain RT (adjusted odds ratio [OR] 1.48 [95% confidence interval [CI] 1.03–2.13; p = 0.0355]) and normofractionated RT (adjusted OR 1.88 [95% CI 1.06–3.31; p = 0.0298]) were associated with increased odds of severe global fatigue. In addition, there was a significant association between normofractionated RT (adjusted OR 1.849 [95% CI 1.04–3.3; p = 0.0354]) and an increased likelihood of severe physical fatigue. Conclusion: We found a significant association between internal mammary chain RT (versus No), normofractionated RT (versus hypofractionated RT) and increased likelihood of persistent severe global fatigue. Our data add to the current understanding of treatment-related factors affecting fatigue after BC and could lead to personalised interventions to improve the prevention and management of this disabling symptom. Highlights: About one-third of breast cancer survivors experience persistent severe fatigue. Radiation therapy (RT) modalities are associated with severe global fatigue. Internal mammary chain RT is associated with severe global fatigue at 1 year. Normofractionated RT is associated with severe global fatigue at 1 year. RT modalities are not associated with emotional and cognitive fatigue dimensions.